2013
DOI: 10.2174/1574887111308010005
|View full text |Cite
|
Sign up to set email alerts
|

Skin Benefits with a Novel Emollient-Treated Menstrual Pad

Abstract: Manufacturers of consumer products consistently seek to improve marketed products in terms of both safety and efficacy. The desire for continued improvement is seen even in well-established products such as catamenial products which have existed in some form for thousands of years. A recent innovation in the design of menstrual pads is the addition of a surface finish of emollient for the purpose of increasing comfort during wear. The present paper presents different evaluations of such an emollient-treated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…jensenii being present in the vaginal microbiome increasing from 37.4% to 60.7% with use of panty liners during menstruation. While the directionality of this relationship is not immediately intuitive, previous work has shown that use of emollient pads changes the vaginal epithelium and that some women’s vaginal microflora does shift with pad versus tampon use [ 66 , 67 ], although the evidence on this is mixed [ 68 ]. NMDS/ANOSIM testing indicated that tampon use was associated with the vaginal microbiome, lending further support to the hypothesis that menstrual habits could impact the microbiome ( S5 and S6 Files).…”
Section: Resultsmentioning
confidence: 99%
“…jensenii being present in the vaginal microbiome increasing from 37.4% to 60.7% with use of panty liners during menstruation. While the directionality of this relationship is not immediately intuitive, previous work has shown that use of emollient pads changes the vaginal epithelium and that some women’s vaginal microflora does shift with pad versus tampon use [ 66 , 67 ], although the evidence on this is mixed [ 68 ]. NMDS/ANOSIM testing indicated that tampon use was associated with the vaginal microbiome, lending further support to the hypothesis that menstrual habits could impact the microbiome ( S5 and S6 Files).…”
Section: Resultsmentioning
confidence: 99%